130 mA mm−1β-Ga2O3 metal semiconductor field effect transistor with low-temperature metalorganic vapor phase epitaxy-regrown ohmic contacts. (22nd June 2021) - Bhattacharyya, Arkka; Roy, Saurav; Ranga, Praneeth; Shoemaker, Daniel; Song, Yiwen; Lundh, James Spencer; Choi, Sukwon; Krishnamoorthy, Sriram
Abstract: We report on the first demonstration of metalorganic vapor phase epitaxy-regrown (MOVPE) ohmic contacts in an all MOVPE-grown β -Ga2 O3 metal semiconductor field effect transistor (MESFET). The low-temperature (600 °C) heavy (n + ) Si-doped regrown layers exhibit extremely high conductivity with a sheet resistance of 73 Ω/□ and a record low metal/n + -Ga2 O3 contact resistance of 80 mΩ·mm and specific contact resistivity of 8.3 × 10 −7 Ω·cm 2 were achieved. The fabricated MESFETs exhibit a maximum ON current of 130 mA mm −1 and a high I ON / I OFF ratio of >10 10 . Thermal characterization was also performed to assess the device self-heating under the high current and power conditions.